Subcutaneous immunoglobulin for maintenance treatment in chronic inflammatory demyelinating polyneuropathy (PATH): a randomised, double-blind, placebo-controlled, phase 3 trial. Issue 1 (January 2018) - van Schaik, Ivo N; Bril, Vera; van Geloven, Nan; Hartung, Hans-Peter; Lewis, Richard A; Sobue, Gen; Lawo, John-Philip; Praus, Michaela; Mielke, Orell; Durn, Billie L; Cornblath, David R; Merkies, Ingemar S J; et al.
Summary: Background: Approximately two-thirds of patients with chronic inflammatory demyelinating polyneuropathy (CIDP) need long-term intravenous immunoglobulin. Subcutaneous immunoglobulin (SCIg) is an alternative option for immunoglobulin delivery, but has not previously been investigated in a large trial of CIDP. The PATH study compared relapse rates in patients given SCIg versus placebo. Methods: Between March 12, 2012, and Sept 20, 2016, we studied patients from 69 neuromuscular centres in North America, Europe, Israel, Australia, and Japan. Adults with definite or probable CIDP who responded to intravenous immunoglobulin treatment were eligible. We randomly allocated participants to 0·2 g/kg or 0·4 g/kg of a 20% SCIg solution (IgPro20) weekly versus placebo (2% human albumin solution) for maintenance treatment for 24 weeks. We did randomisation in a 1:1:1 ratio with an interactive voice and web response system with a block size of six, stratified by region (Japan or non-Japan). The primary outcome was the proportion of patients with a CIDP relapse or who were withdrawn for any other reason during 24 weeks of treatment. Patients, caregivers, and study personnel, including those assessing outcomes, were masked to treatment assignment. Analyses were done in the intention-to-treat and per-protocol sets. This trial is registered withClinicalTrials.gov, numberNCT01545076 . Findings: In this randomised, double-blind, placebo-controlled trial, we randomly allocated 172 patients: 57 (33%) to the placebo group, 57 (33%) to the low-dose group, and 58 (34%) to the high-dose group. In the intention-to-treat set, 36 (63% [95% CI 50–74]) patients on placebo, 22 (39% [27–52]) on low-dose SCIg, and 19 (33% [22–46]) on high-dose SCIg had a relapse or were withdrawn from the study for other reasons (p=0·0007). Absolute risk reductions were 25% (95% CI 6–41) for low-dose versus placebo (p=0·007), 30% (12–46) for high-dose versus placebo (p=0·001), and 6% (−11 to 23) for high-dose versus low-dose (p=0·32). Causally related adverse events occurred in 47 (27%) patients (ten [18%] in the placebo group, 17 [30%] in the low-dose group, and 20 [34%] in the high-dose group). Six (3%) patients had 11 serious adverse events: one (2%) patient in the placebo group, three (5%) in the low-dose group, and two (3%) in the high-dose group; only one (an acute allergic skin reaction in the low-dose group) was assessed to be causally related. Interpretation: This study, which is to our knowledge, the largest trial of CIDP to date and the first to study two administrations of immunoglobulins and two doses, showed that both doses of SCIg IgPro20 were efficacious and well tolerated, suggesting that SCIg can be used as a maintenance treatment for CIDP. Funding: CSL Behring.